Konflikty w rozwoju przestrzennym Lublina - studium przypadku - Gorzym-Wilkowski, Waldemar A. (Conflicts in Space Development of Lublin - a Case Study, 2006)
The socio-economic development on the local level is determined to a large extent by the local development. It is necessary to take into account natural mechanisms of space transformation and the possibilities of impact of the authorities on space. The impact of authorities is oriented first of all towards the configuration of space order and finding the proper conditions to localizing objects connected with public functions (education, communication, recreation etc). Those purposes are often the reason of conflicts with estate's owners, whose purpose is to maximize the economic benefit. As the research carried out in Lublin has shown that the source of the most frequent conflicts are the public functions which occupy most of space - roads, public services and public green areas. Another source of conflict can also be the attempts of the suppression of the extensive expansion of space development on open areas. Legal mechanisms of local governments allow to solve those type of conflicts in public interest. Nevertheless the nature of social and economic space development on the one hand and on the other hand limited impact of local governments on space by means of financial instruments - all those factors cause fixed growth in the number and plurality of space conflicts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 284-292